2011
DOI: 10.1016/j.jjcc.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae heat shock protein 60 is associated with apoptotic signaling pathway in human atheromatous plaques of coronary artery disease patients

Abstract: Genes/proteins of pre-apoptotic caspase dependent/independent pathways, chemokines, and inflammatory cytokines receptors were significantly up-regulated in human atheromatous plaques of cHSP60 positive CAD patients suggesting an association of cHSP60 with CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…In both Mycoplasma pneumoniae and Mycoplasma genitalium infection, GroEL is associated with adherence, complementing adhesion proteins like HMW1 and P1. In addition, Chlamydophila pneumoniae Hsp60 was reported to have an association with the apoptotic signaling pathway, and in some patients with Hsp60-positive coronary artery disease, proapoptotic genes or proteins exhibit high expression (26). Similar results were observed in our study: GroEL of M. gallisepticum not only attached to the host cells but also upregulated the expression of apoptosis-related caspase proteins (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…In both Mycoplasma pneumoniae and Mycoplasma genitalium infection, GroEL is associated with adherence, complementing adhesion proteins like HMW1 and P1. In addition, Chlamydophila pneumoniae Hsp60 was reported to have an association with the apoptotic signaling pathway, and in some patients with Hsp60-positive coronary artery disease, proapoptotic genes or proteins exhibit high expression (26). Similar results were observed in our study: GroEL of M. gallisepticum not only attached to the host cells but also upregulated the expression of apoptosis-related caspase proteins (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…30,31 Polygenetic analysis has reported that rs6734238 in the IL1F10/IL1RN locus was found to be significantly associated with coronary artery disease. 32 Additionally, in atherosclerotic plaques of patients with coronary heart disease (CAD), 33 We previously reported that circulating IL-38 was increased in STEMI patients, which indicated that IL-38 may act as a promotive role in the development of MI. 20 In this study, we observed that administration of rIL-38 in mice ameliorated ventricular remodelling via suppressing infiltration of inflammatory cells and inhibiting proinflammatory cytokines in the post-MI hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, polymorphisms in IL-38 were associated with CRP concentrations in humans [23] and were found to be significantly associated with coronary artery disease (CAD) [24]. In addition, IL-38 mRNA was found in human atheromatous plaques of coronary artery disease patients [25]. These results suggest an important role for IL-38 in cardiovascular diseases, indicating that IL-38 might also play an important role in hyperlipidemia which contributes to cardiovascular disease development.…”
Section: Introductionmentioning
confidence: 89%